Towards stable and efficient electrolytes for room-temperature rechargeable calcium batteries. Issue 12 (28th August 2019) - Li, Zhenyou; Fuhr, Olaf; Fichtner, Maximilian; Zhao-Karger, Zhirong
Abstract : A novel Ca electrolyte with a broad electrochemical window and high ionic conductivity is demonstrated. Abstract : Rechargeable calcium (Ca) batteries have the prospect of high-energy and low-cost. However, the development of Ca batteries is hindered due to the lack of efficient electrolytes. Herein, we report novel calcium tetrakis(hexafluoroisopropyloxy)borate Ca[B(hfip)4 ]2 based electrolytes exhibiting reversible Ca deposition at room temperature, a high oxidative stability up to 4.5 V and high ionic conductivity >8 mS cm −1 . This finding opens a new approach towards room-temperature rechargeable calcium batteries.